If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -9 = 3(2x + -6) Reorder the terms: -9 + 3x = 3(2x + -6) Reorder the terms: -9 + 3x = 3(-6 + 2x) -9 + 3x = (-6 * 3 + 2x * 3) -9 + 3x = (-18 + 6x) Solving -9 + 3x = -18 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -9 + 3x + -6x = -18 + 6x + -6x Combine like terms: 3x + -6x = -3x -9 + -3x = -18 + 6x + -6x Combine like terms: 6x + -6x = 0 -9 + -3x = -18 + 0 -9 + -3x = -18 Add '9' to each side of the equation. -9 + 9 + -3x = -18 + 9 Combine like terms: -9 + 9 = 0 0 + -3x = -18 + 9 -3x = -18 + 9 Combine like terms: -18 + 9 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 1=-3+X/2 | | xy-1=3y | | 4e-4=2e+8 | | X-(1/y)=3 | | x/15-11 | | -0.5(y-12)=-0.1(y+1) | | 0=2x^2-5x+3 | | 3x^-4/27x^2 | | 1/2x+5/3=-3/2x-7/3 | | 2(x-5)=x+5x | | (x^2-4x+4)/(x^2+4x-12)*(2x+12)/(6x^2-13x+2) | | s^2+6s+5=0 | | (2/x)+4=(2/3x) | | 8m-29=-22+7m | | 13.7b-6.5=23b+8.3 | | 5n-25=-13+3n | | -7.64+10000= | | y=-3*1+2 | | y=-3*-2 | | 0.6(y+1.5)=-2.1(y-3) | | 6(3+3x)-2=106 | | -2/5(n-1/8)=1/2(n-1/6) | | 10-2m=3m+25 | | 1729x-258=433x-474 | | (2/x^2+12x+36)+(5/x^2+x-30) | | X^2+10x+9=(x+1)(ax+b) | | -2(x-3)+4(2-x)= | | -5y-8=-7y-16 | | 19x-11-17x+14=2x+3 | | [5x-7]=33 | | 8-[(-3+7)-(3-9)]= | | 5+4x-7=4x-2 |